Sincere and Insincere Arguing - Dalla Rosa, Davide; Mancini, Filippo (Informal Logic, 2024)
In this paper, we contend that there are two ways of arguing, namely sincere and insincere arguing. We draw such a distinction, based on the felicity conditions of the complex speech act of arguing as modelled in van Eemeren and Grootendorst’s pragma-dialectical approach. We introduce a conversational setting, which contains a speech act of arguing that does not count as insincere arguing, while being a sui generis form of sincere arguing. We designate it as “cooperative inquiry”. Finally, we show that argument evaluation plays a key role in determining whether an instance of arguing counts as either arguing sincerely or insincerely.